Report on the future conversations workshop at CHIIR 2021 - Spina, Damiano; Trippas, Johanne R; Thomas, Paul; Joho, Hideo; Byström, Katriina; Clark, Leigh; Craswell, Nick; Czerwinski, Mary; Elsweiler, David; Frummet, Alexander; Ghosh, Souvick; Kiesel, Johannes; et al. (SIGIR Forum, 2021)
The Future Conversations workshop at CHIIR'21 looked to the future of search, recommendation, and information interaction to ask: where are the opportunities for conversational interactions? What do we need to do to get there? Furthermore, who stands to benefit? The workshop was hands-on and interactive. Rather than a series of technical talks, we solicited position statements on opportunities, problems, and solutions in conversational search in all modalities (written, spoken, or multimodal). This paper — co-authored by the organisers and participants of the workshop — summarises the submitted statements and the discussions we had during the two sessions of the workshop. Statements discussed during the workshop are available at https://bit.ly/FutureConversations2021Statements.